Dominican Resonances in Medieval Iceland
1 online resource.
Keywords: This book explores the life and times of Jón Halldórsson, bishop of Skálholt (1322-39), a Dominican who had studied the liberal arts and canon law in Paris and Bologna. An innovator in legendary sagas, the book examines his life, context and legacy from the perspectives of literary history, clerical culture, administrative literacy, liturgy, and manuscript studies, in order to provide a general view of the conditions under which literate culture thrived in 14th-century Scandinavia. It contains chapters treating Halldórsson's learning and writing, as well as studies of more general aspects of literacy. The combination of various perspectives offers a snapshot with wider implications for our understanding of medieval literacy. Contributors (in order of appearance) are Christian Etheridge, Viðar Pálsson, Gottskálk Jensson, Hjalti Snær Ægisson, Védís Ragnheiðardóttir, Stefan Drechsler, Karl G. Johansson, Astrid Marner, Gisela Attinger, Embla Aae, and Gunnar Harðarson.